The profile of the outside hitter in male volleyball - Cojocaru, A.-M.; Cojocaru, M. (Journal of Sport and Kinetic Movement, 2017)
The developmental trends of the current game determine all those involved in the performance activity to look for and to find new ways of playing the game in order to play as efficient and spectacular as possible. In the performance and high-performance game, the players who are playing on this position are those who participate in all game stages, and depending on their performance, they can influence the winning or the loss chances of the game. The aim of the thesis is to analyse the parameters of the best players on this position in the world in order to create a national-level model. The hypothesis of the thesis is that the achievement of certain higher parameters of the players on this position may negatively or positively influence the winning of sets or games. The research methods were the bibliographic study, statistical-mathematical method, and the graphic representation method. All the qualities and skills of the athlete are in complex relationships both with each other and between these and the game effectiveness. They change differently in the sports training process and they guide us in the fair appreciation of these (the skills) in the selection process. In conclusion, the average profile of the best players on this position has achieved real values, which can be considered worthwhile landmarks in the selection of players for the position of outside hitter, and which have made a significant contribution to winning the games.